2019
DOI: 10.1038/s41467-019-11312-8
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell CAS-seq reveals a class of short PIWI-interacting RNAs in human oocytes

Abstract: Small RNAs have important functions. However, small RNAs in primate oocytes remain unexplored. Herein, we develop CAS-seq, a single-cell small RNA sequencing method, and profile the small RNAs in human oocytes and embryos. We discover a class of ~20-nt small RNAs that are predominantly expressed in human and monkey oocytes, but not in mouse oocytes. They are specifically associated with HIWI3 (PIWIL3), whereas significantly shorter than the commonly known PIWI-interacting RNAs (piRNAs), designated as oocyte sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
148
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(162 citation statements)
references
References 69 publications
14
148
0
Order By: Relevance
“…In accordance with previous findings 10,11 , in the present study we observed a reduced oocyte developmental competence in the NBS, as indicated by decreased cleavage and blastocyst rates after in vitro fertilization (IVF), and this was associated to changes in miRNA and transcriptomic profiles both in OOs and FCs. Being miRNAs only one of the small RNA components, as expected those identified in buffalo represent only a fraction of the total small non-coding RNA present in both OOs and FCs 27,28 . The overall miRNA expression pattern was different between OOs obtained in the two seasons.…”
Section: Discussionsupporting
confidence: 55%
“…In accordance with previous findings 10,11 , in the present study we observed a reduced oocyte developmental competence in the NBS, as indicated by decreased cleavage and blastocyst rates after in vitro fertilization (IVF), and this was associated to changes in miRNA and transcriptomic profiles both in OOs and FCs. Being miRNAs only one of the small RNA components, as expected those identified in buffalo represent only a fraction of the total small non-coding RNA present in both OOs and FCs 27,28 . The overall miRNA expression pattern was different between OOs obtained in the two seasons.…”
Section: Discussionsupporting
confidence: 55%
“…Recently, it has been reported that, in human oocytes, PIWIL3 associates with a group of relatively short~20 nt piRNAs. We have not detected these short piRNAs in bovine oocytes, and it remains to be established whether piRNA size may be species-dependent [44]. piRNAs from oocytes and TDRKH-IPs map uniquely to intergenic regions of the genome, forming large piRNA clusters.…”
Section: Discussionmentioning
confidence: 82%
“…For meiosis and retrotransposon silencing in oocytes, a subclass of siRNAs (endogeneous-siRNAs) known to regulate transcripts [ 103 , 104 ] is necessary [ 105 , 106 ]. However, an oocyte-specific piRNA family (os-piRNAs) may also be involved in the silencing of TEs, as revealed in human oocytes [ 107 ]. The repression of transposable elements is indeed important for oogenesis, seeing as a higher proportion of oocytes from mice expressing elevated levels of retrotransposons undergo apoptosis during meiotic prophase I [ 108 ].…”
Section: Epigenetic Reprogramming During Oogenesismentioning
confidence: 99%